Fast-Food Marketing Strategies And Their Impact On Childhood Obesity - Herédia, Afonso M.; Hipólito, João; Nunes, Odete; Ribeiro, Luísa; Moura, Tatiana; Laneiro, Tito (Journal of Tourism, Sustainability and Well-being, 2017)
Overweight and obesity are growing health problems in children. The increase in fast-food consumption has greatly contributed to this phenomenon. Children are a frequent target for fast-food advertising, and the television is one of the most used marketing channels. We assessed the frequency of fast-food ingestion, television viewing time and body mass index (BMI) in children from 8 to 12 years of age. A quantitative approach was followed, using a self-report questionnaire. The sample was composed of 60 children with an age average of 9.88 years (SD=1.37). It was found that longer television viewing times were associated with higher frequency of fast-food ingestion for both school days (rS = 0.54, p < .001) and weekends/holidays (rS = 0.50, p < .001). A positive and moderate correlation between television viewing times and BMI (rS = 0.51, p < .001; rS = 0.55, p < .001) was also observed. The results indicate that television advertising makes children wanting to try the fast-food advertised (67%; n = 40), and ask parents to buy it (60%; n = 36). The good taste (72%; n = 43) and the gifts (38%; n = 23) are what the children in our study most appreciate in fast-food restaurants. Despite legal regulatory mechanisms, marketing continues to have a strong impact on the promotion of fast-food consumption in children.